Calcium and phosphorus solubility in neonatal intravenous feeding solutions. Issue 4 (April 1990) - MacMahon, P; Mayne, P D; Blair, M; Pope, C; Kovar, I Z
Abstract : The limited solubility of calcium and phosphorus in standard parenteral nutrition formulations has restricted the ability to provide sufficient minerals to preterm infants to prevent substrate deficient metabolic bone disease. We determined the solubility limits of calcium and phosphorus in a total of 160 formulations under carefully controlled conditions. By increasing the concentrations of dextrose, amino acids, and by using Addiphos instead of 8.7% dipotassium hydrogen phosphate as the phosphorus source, higher concentrations of both calcium and phosphorus were held in solution. This should permit the delivery of increased concentrations of these minerals at rates which approximate fetal accretion.